THE INFLUENCE OF FINANCIAL LITERACY AND MENTAL ACCOUNTING ON FINANCIAL MANAGEMENT OF UMKM IN DELI TUA DISTRICT - Endang Saputri Br Sembiring; Fauziah Rahman (RADJA PUBLIKA, 2025)
This study aims to determine the effect of financial literacy and mental accounting on financial managementMSMEs in Deli Tua sub-district. This research uses a quantitative approach, which involves processing primary and secondary data where primary data is obtained from respondents' answers to questions or statements in questionnaires distributed directly while secondary data in this study comes from the website of the Deli Serdang Cooperative and UKM Office. The sample in this study were MSME actors in Deli Serdang, totaling 97 respondents. The method used for data analysis uses SPSS for windows software. The results of this study indicate that the Financial Literacy Variable (X1) has a positive and significant effect on MSME financial management (Y), Financial Inclusion (X2) has a significant and significant effect on MSME financial management (Y). From the F test, Financial Literacy and Financial Inclusion together have a positive and significant effect on MSME financial management. The Adjusted R square value is 0.566, this figure indicates that 87% shows that the effect of financial literacy and financial inclusion on financial management is 87%, the remaining 13% is influenced by other variables or factors not examined in this study.